The role of vegetarian diet in Nephrolithiasis - Zinkow-Krzemyk, Karolina; Kotuła, Jacek; Kapler, Marta; Mąsior, Magdalena Natalia; Świerczek, Izabella (Quality in Sport, 2024)
Nephrolithiasis, commonly known as kidney stone disease, is a prevalent condition with significant morbidity worldwide. Notably, this medical condition is strongly influenced by nutritional habits. Dietary choices play a critical role in both the formation and prevention of kidney stones, highlighting the importance of proper nutrition in managing this disease. This review explores the impact of a vegetarian diet on nephrolithiasis. Evidence suggest that plant-based diets, which excludes animal protein, may contribute to a reduced risk of kidney stone formation. Vegetarian diet could be also considered as higher in fruits and vegetables, so in conclusion, people on plant-based diet have a water-rich food intake. Not only the fluid intake, but also the balance of calcium and oxalates is very important in managing risk of forming kidney stones. This diet typically result in lower acid load, higher urinary pH and increased urinary citrate levels. Everything mentioned is a key preventive strategy against kidney calculi. Nephrolithiasis has undenyable colligation with diet. Patients dietary choices and their lifestyle could strongly influence the course of this disease. Overall, well-planned vegetarian diet may offer protective benefits against nephrolithiasis. It should be individualized and preferably prepared by a professional dietitian. In this case, it is important to remember that our diet plays role similarly in genesis as in recurrence of kidney stone disease. Changing eating habits aims to reduce lithogenic risk factors.